MONITORING OF THE FOREST EVOLUTION IN REMNATS OF THE ATLANTIC FOREST BIOME USING RAPIDEYE IMAGERY - Marchesan, Juliana; Alba, Elisiane; Mello, Eliziane Pivoto; Pedrali, Letícia Daiane; Badin, Tiago Luis; Pereira, Rudiney Soares (Scientia Agraria, 2018)
This study was aimed towards analizing the space-time evolution of the forest covering of the Atlantic Forest biome in extremely high priority area for the preservation of biodiversity located in the central region of Rio Grande do Sul, between the years of 2011 and 2013. The mapping of land user and cover was accomplished by means of the Bhattacharya supervised assortment, utilizing RapidEye imagery in the years of 2011 and 2013. The spatialization of the forest dinamics was accomplished by identifying the upkeep, expansion and deforestation areas during the analysis period. The agriculture presented the highest evolution percentage, presenting a 11.89% increase, whereas the forest coverage presented an 8.21% decrease. The evolutionary analysis of the forest coverage demonstrated that the forest deforestation was of a 6.31% and the expansion of native forests was of 4.30%. The spatial analysis presented high potential in identifying spots of alteration of the natural vegetation of the Atlantic Forest Biome in large scale. Therefore, this tool can be used along with the policies of preservation of the natural ecosystems.